Aqueous Synthesis and Characterization of CdSe/ZnO Core-Shell Nanoparticles. (1st November 2011) - Rakgalakane, B. P.; Moloto, M. J.
Abstract : Core-shell nanomaterials based on CdSe as the core and ZnO as the shell were prepared using an aqueous route involving the use of Cd salt and NaBH4 in reaction with Se to generate CdSe in the presence of thioglycerol (TG) as a stabilizer. ZnO has been prepared at pH 12 using stronger base such as NaOH at lower concentration and by varying amounts of Zn 2+ ions ranging from 2.5, 5, 25 mL, and 50 mL to prepare core-shell nanomaterials. The absorption and emission spectral features are dominated by CdSe nanoparticles with typical shift in the emission maxima red-shifted in relation to the band edges. There is an observable change in the band edge from the core as the amount of ZnO is increased. The TEM features showed the formation of the core-shell from the volume of 5 mL which is indicated by the thin layer of shell on the surface of the CdSe core.